2015
DOI: 10.1016/j.scr.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation dose alters the dynamics of human neural stem cell engraftment, proliferation and migration after spinal cord injury

Abstract: The effect of transplantation dose on the spatiotemporal dynamics of human neural stem cell engraftment has not been quantitatively evaluated in the central nervous system. We investigated changes over time in engraftment/survival, proliferation, and migration of multipotent human central nervous system-derived neural stem cells (hCNS-SCns) transplanted at doses ranging from 10,000 to 500,000 cells in spinal cord injured immunodeficient mice. Transplant dose was inversely correlated with measures of donor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 50 publications
3
38
0
Order By: Relevance
“…A significant positive correlation was observed between transplant dose and number of human cells in the SCI microenvironment (Figure 1C), suggesting a linear relationship between these factors. However, there was a significant improvement in goodness of fit when a second-order polynomial was applied to the dataset containing all dose groups ( r 2  = 0.7, p ≤ 0.02 versus r 2  = 0.6, p ≤ 0.8), which was not apparent when the very-high-dose group was eliminated from the dataset; ( r 2  = 0.7, p ≤ 1.0), suggesting a plateau of donor cell engraftment at the highest (500,000 cells) transplant dose (Piltti et al., 2015). This change was not related to differences in either cell death, as assessed by cleaved CASP3, or proliferation, as assessed by SC121 + /MKI67 + human cells, as no significant differences were observed in these measures between groups (Piltti et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant positive correlation was observed between transplant dose and number of human cells in the SCI microenvironment (Figure 1C), suggesting a linear relationship between these factors. However, there was a significant improvement in goodness of fit when a second-order polynomial was applied to the dataset containing all dose groups ( r 2  = 0.7, p ≤ 0.02 versus r 2  = 0.6, p ≤ 0.8), which was not apparent when the very-high-dose group was eliminated from the dataset; ( r 2  = 0.7, p ≤ 1.0), suggesting a plateau of donor cell engraftment at the highest (500,000 cells) transplant dose (Piltti et al., 2015). This change was not related to differences in either cell death, as assessed by cleaved CASP3, or proliferation, as assessed by SC121 + /MKI67 + human cells, as no significant differences were observed in these measures between groups (Piltti et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…However, there was a significant improvement in goodness of fit when a second-order polynomial was applied to the dataset containing all dose groups ( r 2  = 0.7, p ≤ 0.02 versus r 2  = 0.6, p ≤ 0.8), which was not apparent when the very-high-dose group was eliminated from the dataset; ( r 2  = 0.7, p ≤ 1.0), suggesting a plateau of donor cell engraftment at the highest (500,000 cells) transplant dose (Piltti et al., 2015). This change was not related to differences in either cell death, as assessed by cleaved CASP3, or proliferation, as assessed by SC121 + /MKI67 + human cells, as no significant differences were observed in these measures between groups (Piltti et al., 2015).
Figure 1Transplantation of hCNS-SCns in Early Chronic SCI, at 30 dpi, Results in a Linear Increase in Engraftment that Is Positively Correlated with Initial Transplantation Dose(A) Representative coronal spinal cord sections immunostained for SC121 (STEM121) and hematoxylin 16 WPT.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the field of stroke, although a variety of benefits have been reported, integration with the host has not been demonstrated. Also unresolved are the questions of optimal dosing and dose scaling to man; this is a tricky issue because, at least based on our experience on spinal cord injury, dose escalation alters the dynamics of engraftment, migration, and fate (19). Even less can be said about stem cell therapies for models of DAI, although the field can borrow from spinal cord injury that invariably involves trauma in axonal tracts.…”
Section: Special Considerations For Focal Tbi and Daimentioning
confidence: 99%
“…A considerable amount of studies demonstrated that NSCs could repair the damage of central or peripheral nervous system. [10][11][12][13][14] However, transplantation of NSCs has shortcomings: the survival rate of NSCs is low; 15 most NSCs differentiate into astrocytes; and cavities are observed to exist after NSCs transplantation. 10,11,16,17 Another important factor in tissue engineering is growth factors.…”
mentioning
confidence: 99%